SPRAWA LOCKERBIE: KOMPROMISOWY I UNIKALNY CHARAKTER ROZWIĄZANIA MIĘDZYNARODOWEGO - Płachta, Michał; Dąbek, Aleksandra (Wydział Prawa i Administracji UAM, 2003)
The article presents a discussion of the once famous Boeing 747 crash that killed 270 people - 243 passangers, 16 crewmembers and 11 citizens of the Lockerbie town in southern Scotland. The disaster was caused by a terrorist attack organised by two Libyans. The authors present the complex process of preparation for the trial, analyzing in detail their political, legal and social conditions that led to its internationally unique end: sentencing the defendants by a Scotish court in the territory of the Netherlands.
LOCKERBIE CASE AS UNIQUE INTERNATIONAL COMPROMISE